Estudos sobre a embriogênese somática e a regeneração para duas cultivares de mandioca (Manihot esculenta Crantz) cultivadas no estado do Ceará - Bastos, João Luiz Pinheiro (2003)
Primary somatic embryogenesis, secondary somatic embryogenesis (cyclic) and shoot organogenesis protocols, were developed, for 2 genotypes of cassava plants – Tapicínea and Bujá Preta, cultivated in the state of Ceará. Cultures were established, using shoot apical meristems of plants maintained in the field, and using the basic MS medium, supplemented with sucrose, copper sulfate and agargel. The material was maintained by monthly sub-culture as in vitro shoot, using nodal explants and cultured on MS medium without growth regulators. Apical shoot meristems from in vitro plants, with 2 or 3 immature leaves were used for induction of primary somatic embryos, on basic medium, supplemented with Picloram. That growth regulator was capable to induce the embryos formation in different concentrations, being the 8,0 mg/L concentration, the most appropriate for the 2 genotypes. The embryos were, then, transferred to maturation medium (MS + 0,1 mg/L of BAP). Cotyledons from germinating primary somatic embryos were used to induction secondary (cyclic) somatic embryos, in MS medium supplemented with different Picloram concentrations. A larger competence was observed for the embriogênese in that explante type, when compared to shoot apexes, in both, frequency and productivity. The most appropriate concentrations for the 2 genotypes were 4,0 mg/L and 8,0 mg/L - Tapicínea and Bujá Preta, respectively. Pieces of cotyledons from secondary somatic embryos were used in the shoot organogenesis induction. The explantes were inoculated in MS medium, supplemented with IBA and BAP (0,0; 0,25; 0,5; 1,0 and 3,0 mg/L, for both regulators), in factorial (5 x 5) arranged. The positive answer was observed in both genotypes, being the concentrations of IBA and BAP of 1,0 mg/L and 0,25 mg/L, and of 1,0 mg/L and 0,5 mg/L, the best for Bujá Preta and Tapicínea, respectively. The histological analysis of secondary somatic embryogenesis – Bujá Preta cultivar - showed an embryogenics cells proliferation, starting from the vascular areas. Globular structures appeared starting from that cellular mass, configuring the multicelular origin of the embryos. Histological analysis of the shoot organogenesis, also in Bujá, Preta cultivar, presented different result compared to embryogenesis. The structures formation occur in sub-epidermal layers, forming buds that development in to shoots, with a vascular connection from the explante